Research on Well-Being: Determinants, Effects, and its Relevance for Management - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2017)
Empirically orientated happiness research provides valuable and new insights to both business and political economics. Managers can benefit from the knowledge gained regarding the determinants and even more from the consequences of subjective well-being. They should, however, not engage in directly trying to raise the happiness of stakeholders. Rather, they should lay the ground for the respective persons being able to reach happiness in the way they choose themselves. Research on well-being provides crucial insights for economic and social policy as well as for business economics considering aspects such as recognition, autonomy, health, personal relationships and political institutions.
Keywords: 330; Happiness; well-being; life satisfaction; business; management